2014
DOI: 10.1021/ma500500q
|View full text |Cite
|
Sign up to set email alerts
|

The Polyelectrolyte Complex/Coacervate Continuum

Abstract: Stoichiometric polyelectrolyte complexes (PECs) of the strong polyelectrolytes poly­(styrenesulfonate) (PSS) and poly­(diallyldimethylammonium) (PDADMA) were dissociated and dissolved in aqueous KBr. Water was added to dilute the salt, allowing polyelectrolytes to reassociate. After appropriate equilibration, these mixtures yielded compositions spanning complexes (solid) to coacervates (elastic liquid) to dissolved solutions with increasing [KBr]. These compositions were defined by a ternary polymer/water/salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

43
749
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(797 citation statements)
references
References 50 publications
43
749
5
Order By: Relevance
“…Rheological characterization demonstrated that these trends correlate with decreasing coacervate viscosity with increasing salt concentration ( Figure 5a) [71,79,157]. Furthermore, the viscosity was seen to increase as a function of degree of polymerization ( Figure 5b) [79], as would be expected for polymeric materials.…”
Section: Viscositymentioning
confidence: 55%
“…Rheological characterization demonstrated that these trends correlate with decreasing coacervate viscosity with increasing salt concentration ( Figure 5a) [71,79,157]. Furthermore, the viscosity was seen to increase as a function of degree of polymerization ( Figure 5b) [79], as would be expected for polymeric materials.…”
Section: Viscositymentioning
confidence: 55%
“…147 The entropic forces also arise from reorganization of water molecules around the polymer chains during the complexation process as evidenced in recent experiments. 55 …”
Section: Electrostatically Driven Structure In Polyelectrolyte Solutionsmentioning
confidence: 99%
“…Furthermore, the nature of the charged species must allow for the formation of a 'coacervate', which represents a subset of complexes that undergo a liquid-liquid phase separation rather than forming solid precipitates. [1][2][3][4][5][6] Historical and current investigations into complex coacervates have studied the formation of such phases in natural polymers, such as proteins or polysaccharides, which are currently widely used as food additives. [7][8][9][10][11][12][13][14][15][16][17][18] Despite the utility of these systems, there has only recently been a resurgence of interest in their molecular behavior, in particular for its promise as a powerful route to self-assembled materials such as micelles, 3,[19][20][21][22] block copolymers, [23][24][25][26] and layer-bylayer assembly.…”
Section: Introductionmentioning
confidence: 99%